Informativeness of the microscopic structures of the diaphysis of the metatarsal bones of female cattle for the forensic and veterinary determination of their age - Yatsenko, I.; Tkachuk, S.; Pasnichenko, O.; Savchuk, L.; Derecha, L. (Scientific Progress & Innovations, 2022)
Based on the analysis of the remains of the skeleton of the limbs, it is possible to establish the species and age of the animal, as well as the peculiarities of the functioning of the movement apparatus during the postnatal period of ontogenesis. Histological studies of bones, in particular the number of microstructures per unit area of the sample, are used to reconstruct the pre-mortem conditions in vertebrates. The aim of the study was to characterize the dynamics of various types of osteons and vascular (Volkmann) channels in the middle third of the diaphysis of the metatarsal bones of cows in the postnatal period of ontogenesis. The material for research was the metatarsal bones of cows of the red-spotted breed from birth to 12 years old. For microscopic studies, sections from the cross-section of the middle of the diaphysis of the metatarsal bones were made according to the generally accepted method. The number of cylindrical-shaped primary and secondary osteons, tertiary, primary and secondary osteons with many channels, their total number and the presence of vascular (Volkmann) channels were studied on the obtained bone section. The number of osteons and Volkmann's canals per unit area of the section of 2.5 mm2 was counted. The dynamics of different types of osteons during the postnatal period of ontogenesis have been established. The number of primary osteons of a cylindrical shape in animals increases from birth to 9 months old, reaching a maximum number, and after 9 months it gradually decreases. The number of secondary osteons of a cylindrical shape and secondary osteons with many channels increases throughout the study period and reaches its maximum value in the period from 120 to 144 months. The number of primary osteons with many canals decreases throughout the studied period. In the age period from 60 to 144 months, tertiary osteons appear in the middle of the diaphysis of the metatarsal bones of cows. The obtained results can be used in forensic veterinary examination to determine the age of cattle during pre-trial investigations.